THE INFLUENCE OF FINANCIAL FACTORS AND LOCAL GOVERNMENT CHARACTERISTICS ON FINANCIAL DISTRESS - Dwi Tia Ningrum; Ria Anisatus Sholihah (Kesatuan Press, 2023)
The success of regional autonomy can be reflected in the quality of the public services provided. This research was conducted in the local government of cities and regencies in Central Java Province. This study aimed to identify and analyze the effect of financial factors and local government characteristics on financial distress in city and district regional governments in Central Java Province for the 2017-2021 period. This research uses causal associative research with a quantitative approach. In determining the sample, a purposive sampling method was used with a population of all regencies and cities in Central Java Province for the 2017-2021 period. This study utilized eight independent variables and data processing instruments used in Microsoft Excel and Econometric Views (E-Views) version 10 with a panel data regression model. This study's results are partially the effectiveness and efficiency ratio that affect financial distress. While the other six variables (income growth ratio, independence ratio, regional solvency ratio, population, and audit opinion) partially do not affect financial distress. However, simultaneously the independent variables affect financial distress.